DETECTION OF FINANCIAL TARGET, FINANCE STABILITY AND EXTERNAL PRESSURE FACTORS ON FRAUDULENT FINANCIAL REPORTING WITH MARKET CAPITALIZATION AS A MODERATOR VARIABLE IN MANUFACTURING COMPANIES - Monika Yovita; Budi Rustandi Kartawinata; Aldi Akbar (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
This study aims to analyze the effect of Financial Target, Financial Stability, and External Pressure on Financial Statement Fraud, with Market Capitalization as a moderating variable, in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period 2017–2019. The research employs a quantitative approach using panel data regression analysis with the Common Effect Model (CEM) and the Moderated Regression Analysis (MRA) technique. The data were obtained from the financial statements of manufacturing companies that met the sampling criteria over a three-year observation period. The results indicate that Financial Target (ROA) has a positive and significant effect on financial statement fraud. Financial Stability (INVSAL and CATA) also shows a significant effect but in different directions: INVSAL increases, while CATA decreases the likelihood of fraudulent financial reporting. External Pressure (FREEC) has a negative and significant effect on financial statement fraud. The moderating variable, Market Capitalization, was found to strengthen the effect of CATA and weaken the effect of INVSAL on financial statement fraud. The R² value of 17.52% indicates that the research model explains a moderate portion of the variation in financial statement fraud among manufacturing firms in Indonesia. These findings support Agency Theory and the Fraud Triangle Theory, suggesting that financial pressure, stability, and external conditions play a crucial role in influencing the occurrence of financial statement fraud.